Ecological strategy of Phyllostachys heteroclada oliver in the riparian zone based on ecological stoichiometry - Jing, Xiong; Su, Wenhui; Fan, Shaohui; Luo, Huiying; Chu, Haoyu (Frontiers in Plant Science, 2022)
The abnormality of seasonal water level fluctuation in the riparian zone may causes various ecological and environmental problems, such as vegetation degradation, biodiversity reduction, soil erosion, and landscape transformation, thereby critically modifying the ecosystem structure and functions. This necessitates the development of a dominant vegetation zone with the potential for competitive. In this study, we investigated the content and distribution pattern of nutrient elements in each organ of the dominant bamboo species, Phyllostachys heteroclada, in the riparian zone. Moreover, we analysed the morphological characteristics, root aeration tissue structure, root oxygen exchange capacity and ATP supply situation, and leaf PSII photosynthetic mechanism of two bamboo species (P. heteroclada and P. nigra) in the riparian zone. Compared with P. nigra, the roots of P. heteroclada formed well-developed oxygen storage and transport structure, i.e. aeration tissue, and exhibited root oxygen secretion in the waterlogging environment of the riparian zone, whereas the roots maintained a high ATP content through energy metabolism, thus benefiting mineral absorption and transport. Moreover, the accumulation of N, P, Ca, Mg, and Fe in the leaves of P. heteroclada was greater under waterlogging conditions than under non-waterlogging conditions, which is the basis for the efficient operation of the photosynthetic mechanism of the leaves. Compared with waterlogged P. nigra, the PSII electron acceptor QA of P. heteroclada leaves had vigorous reducing ability and showed higher efficiency of light uptake energy as well as higher quantum yield indexes φ(Eo) and φ(Po). This study demonstrates that the ecological adaptive regulation strategies of P. heteroclada in the riparian zone are intrinsic driving factors affecting their stoichiometric characteristics, including changes in the absorption and transport of minerals caused by root aeration structure and energy metabolism. Moreover, carbon production and allocation may be caused by the stable photosynthetic mechanism and source–sink relationship of leaves. Through the synergistic regulation of different organs based on realising their roles and functions, P. heteroclada developed ecological stoichiometry characteristics adapted to the riparian zone.